PEMBERIAN DEEP TRANSVERSE FRICTION LEBIH BAIK DARIPADA MASSAGE EFFLEURAGE DALAM MENINGKATKAN LINGKUP GERAK SENDI CERVICAL AKIBAT MYOFASCIAL PAIN SYNDROME OTOT UPPER TRAPEZIUS PADA PEGAWAI LAUNDRY DI DENPASAR TIMUR - Komang Putri Aprilia; I Nyoman Adiputra; Nila Wahyuni (Majalah Ilmiah Fisioterapi Indonesia, 2018)
THE DEEP TRANSVERSE FRICTION INTERVENTION BETTER THAN THE MASSAGE EFFLEURAGE ININCREASING THE RANGE OF CERVICAL MOTION DUE TO OF MYOFASCIAL PAIN SYNDROME OF UPPER TRAPEZIUS MUSCLE ON THE LAUNDRY’S WORKERS IN EAST DENPASAR ABSTRACT Range of Motion (ROM) defined as the extent of joint’s movement that occurs when the joint was moved fromone position to another, either passively or actively. Bad habits that done by someone if it done repeatedly and for along time could trigger pain and tension around the neck as well as decrease in the flexibility of the neck muscles.Decrease in muscle flexibility would result in decreased the range of cervical motion that will interfere with a person'sdaily activities. The purpose of this study was to prove the intervention Deep Transverse Friction better than MassageEffleurage in increasing the range of cervical motion as a result of Myofascial Pain Syndrome in Upper Trapezius muscle.This research was an experimental design with pre and post two group design. These samples included 20 people whowere divided into two groups. Group 1 was given Deep Transverse Friction intervention while group 2 was givenEffleurage Massage intervention. Measurement range of motion was done by goniometer. This research was anexperimental design with pre and post test two group design. The result showed an increase Range of Motion in theintervention Group 1 amounted 4.65 and intervention group 2 amounted 1.35. Paired sample t-test showed a significantresult between intervention group 1 and intervention group 2 with p = 0.000. Difference test between group 1 and group2 using Mann Whitney U-test was obtained p = 0.000. It was concluded that Deep Transverse Friction intervention betterthan Effleurage Massage in increasing the range of cervical motion. Keywords: Range of cervical motion, Deep Transverse Friction, Massage Effleurage, Goniometer.